IoT-based Smart Farming Systems: Techniques, Challenges, and Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The ability of IoT-based smart farming systems to increase crop yields, decrease waste, and increase sustainability is causing them to gain popularity in the agricultural sector. The methods utilized in IoT-based smart farming systems, the difficulties involved in putting them into practice, and successful applications in agriculture are all covered in this research paper's summary. The report also examines new developments in IoT-based smart farming technology and their prospective effects on the agricultural sector. IoT-based smart agricultural systems have many advantages, but they also have drawbacks in terms of cost, technical know-how, connectivity, data privacy, and security. This study explores the advantages and difficulties of IoT-based smart agricultural systems and emphasizes the necessity of cooperation between farmers, technology companies, and governments to meet these difficulties. IoT-based smart agricultural systems appear to have a bright future, but further study is required to fully realize their potential in agriculture.